S34 Lung Function in Children with Sickle Cell Disease. (19th November 2012) - Kirkby, J; Bonner, R; Bates, P; Strunk, R; Kirkham, F; Stocks, J; Sonnappa, S
Abstract : Introduction: Sickle Cell Disease (SCD) is one of the most prevalent genetic diseases with an incidence of ∼1 in 200 Afro-Caribbean children in the UK (WHO; 2006). Since SCD can result in significant respiratory morbidity, [1] lung function tests (LFTs) could play an important role in the clinical management of children with SCD. Aim: To determine the extent to which LFTs identify differences in children with SCD when compared with healthy Black children. Methods: A respiratory health questionnaire was administered, and four commercially available LFTs (Impulse oscillometry (IOS), specific effective airways resistance (sReff), plethysmographic lung volumes, and spirometry) were undertaken in up to 214 healthy Black children and 85 children with SCD aged 4–12y. Results: Amongst children with SCD, 50% reported cough on most days, and 25% had been reviewed by a specialist respiratory consultant within 3 months prior to the assessments. When compared with healthy children, 20% had a reduced total lung capacity (TLC), with concurrent reductions in FEV1 and FVC No differences in sReff were observed and IOS outcomes proved to be of limited value, due to poorly defined limits of normality and large between-subject variability. No significant group differences in bronchodilator responsiveness in SCD or healthy children were observed regardless of the outcome measured (Table 1). Conclusion: Despite the high proportion of respiratory symptoms reported, the number of children with LFTs falling outside the limits of normal was relatively small. Results suggest a pattern of restrictive lung disease in children with SCD. Of the outcomes assessed, baseline spirometry appears to be the most useful for routine assessment of lung disease in young children with SCD. J Caboot, Curr Opin Pediatr 2008 Dencker, Clin Physiol Funct Imaging 2006 Kirkby, ERJ 2010 Kirkby, Ped Pulm 2012 Quanjer, ERJ 2012